Lifestyle education, health education, environmental education, movement - Pálinkás, Réka; Kinczel, Antonia; Miklósi, István; Váczi, Péter; Laoues-Czimbalmos, Nóra; Müller, Anetta (Acta Carolus Robertus, 2022)
Unfortunately, one of the most popular topics today is the diseases of civilization, for which our changed lifestyle is responsible. It is very important that we educate and teach our children to protect nature, pay attention to their environment, move a lot. The role of the family is very important in passing on these values, so it is important and parents have to pay attention to give a good example for their children. In our research, we examined the ecological behavior, environmental values, environmental friendly behaviour and movement habits of students using a questionnaire method. The respondents were seventh and eighth grade students from schools in municipalities of different sizes. (N=558) We used different scales in our questions, such as NEP, PRE, APR, PEB1, HB. To present our results, we used basic statistics and calculated the results of the above-mentioned scales for the type of settlement with the help of SPSS program, analysis of variance (ANOVA). Our results showed that almost half of children believe that they should not respect the laws of nature, however, 71.9% mostly or completely like to go hiking in nature. Protecting ecological behaviour and environmental values is on the right way for students, but we need to draw their attention to becoming more energy efficient. Unfortunately, our results show, as has been supported by several literature, we live a sedentary, inactive life. 62.7% of students attend training that requires physical activity only once or 1-2 times a week. However, 56.7% of them spend at least 2-4 or more hours in front of the computer and / or use their mobilephone every day. Moreover, 33.3% spend 2-4 or more hours in front of the television every day. As at the HB movement scale, we found a difference in student movement as a function of residential settlements F555,2=4.458; p=0.012. If we want our children to live a healthy, quality life, we need to bring up and teach them for that as well.
Keywords: nature; ecological behavior; environmental friendly behaviour; movement